SCHOOL INCLUSION IN SECONDARY SCHOOL: CHALLENGES OF THE TEACHING PRACTICE - Almeida Garcia, Patricia Mara [UNESP]; Diniz, Rosimeire Ferreira [UNESP]; Agostini Martins, Morgana de Fatima (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article presents data from a survey developed as part of a course of the Graduate Program in School Education FCL / CAr Unesp, which aimed to analyze the teaching work in the context of school enrollment at all educational levels. We conducted a survey of high school teachers from a school in Minas Gerais, which met target group of special education students - EEAP. The objective was to observe and analyze how has given the process of inclusion in this school unit, which faced challenges and subsidies offered by the school. Developed a qualitative research, used as a methodological procedure the case study and as research tools use a questionnaire, which was applied to five teachers, conducted observations record in field diary to characterize the school in relation to its physical structure and to understand the pedagogical processes, we analyze the pedagogical Political Project and the dynamics of school organization. The results show, among others, the inclusion of EEAP students in high school is still very fragile, that teachers do not feel prepared and therefore do not make adjustments considering the differences that the PPP is not developed in a collective and participatory manner and that it is necessary an engagement of all school staff in finding the necessary changes.
Keywords: Special education; School inclusion; High school